Interview with Marijke Visser - Silka, Linda (Maine Policy Review, 2024)
An interview with Marijke Visser, the Maine State Library's director of library development. Visser is the winner of the American Library Association 2024 Movers and Shakers Advocates Award recognizing her outstanding work in changing libraries in Maine. She has implemented collaborations and partnerships including, for example, with the Maine Connectivity Authority and the Governor’s Climate Council Equity Subcommittee.